Pengaruh Likuiditas, Perputaran Modal Kerja, dan Leverage Terhadap Profitabilitas Perusahaan BUMN Non-Perbankan Yang Terdaftar di BEI - Fransiska, Benna; Nilwan, Afrizal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The main objective of this research is to study the impact of Leverage (X1), working capital turnover (X2) and liquidity (X3) on profitability (Y) of non-bank public enterprises. products listed on the Indonesia Stock Exchange in 2019 - Period 2021. The research method used is quantitative, with subjects including non-bank public companies that have become public companies from 2019 to 2021. Sampling was carried out using the purposive sampling method, which selected 13 non-bank public enterprises as the research sample. Data analysis was performed using a multiple linear regression model. The results of this study show that liquidity (X1) and working capital turnover (X2) have a significant positive impact on profitability, while Leverage (X3) has a significant negative impact on profitability. These results provide valuable information to stakeholders of non-banking public enterprises in managing their financial aspects to increase profitability and corporate performance.